Development of Lymantria dispar affected by manganese in food - Kula, Emanuel; Martinek, Petr; Chromcová, Lucie; Hedbávný, Josef (Environmental science and pollution research international, 2014)
We studied the response of gypsy moth (Lymantria dispar (Linnaeus) (Lepidoptera: Lymantriidae)) to the content of manganese in food in the laboratory breeding of caterpillars. The food of the caterpillars {Betula pendula Roth (Fagales: Betulaceae) leaves} was contaminated by dipping in the solution of MnCl2 · 4H2O with manganese concentrations of 0, 0.5, 5 and 10 mg ml(-1), by which differentiated manganese contents (307; 632; 4,087 and 8,124 mg kg(-1)) were reached. Parameters recorded during the rearing were as follows: effect of manganese on food consumption, mortality and length of the development of caterpillars, pupation and hatching of imagoes. At the same time, manganese concentrations were determined in the offered and unconsumed food, excrements, and exuviae of the caterpillars, pupal cases and imagoes by using the AAS method. As compared with the control, high manganese contents in the food of gypsy moth caterpillars affected the process of development particularly by increased mortality of the first instar caterpillars (8 % mortality for caterpillars with no Mn contamination (T0) and 62 % mortality for subjects with the highest contamination by manganese (T3)), by prolonged development of the first-third instar (18.7 days (T0) and 27.8 days (T3)) and by increased food consumption of the first-third instar {0.185 g of leaf dry matter (T0) and 0.483 g of leaf dry matter (T3)}. The main defence strategy of the caterpillars to prevent contamination by the increased manganese content in food is the translocation of manganese into frass and exuviae castoff in the process of ecdysis. In the process of development, the content of manganese was reduced by excretion in imagoes to 0.5 % of the intake level even at its maximum inputs in food.
Keywords: larva; Plant Leaves; Moths; stravovací zvyklosti; kukla; Feeding Behavior; Body Weight; Manganese; můry; zvířata; Animals; potraviny; Male; listy rostlin; Larva; mužské pohlaví; chov; mangan; Pupa; tělesná hmotnost; Food; Breeding